An Efficient Substrate-Induced Method for the Synthesis of CF3-Substituted Cyclopropanes by Metal-Free Reaction of Trifluoromethyl Styrylisoxazoles with Nitromethane - Zhao, Qing-he; Yu, Guang-hao; Meng, Ye-chen; Sui, Feng; Yang, Mi-yi; Liu, Li; Li, Hui-jie; Li, Feng; Ma, Hai (Synthesis, 2020)
A series of (trifluoromethyl)cyclopropanes (TFCPs) tolerating a broad range of functional groups, known as tert-butyl bioisosteres, have been obtained from the cyclization reaction between nitromethane and 5-[β-(trifluoromethyl)styryl]isoxazoles in 70–94% yields and 75:25 to 90:10 dr. This method offers practical access to this cyclopropyl moiety of pharmacological interest, employing an inorganic base under phase-transfer conditions.
Keywords: styrylisoxazole; cyclization; trifluoromethyl; cyclopropane; inorganic base; phase-transfer catalyst